PEMAAFAN DAN PROKRASTINASI AKADEMIK MAHASISWA - Rahmandani, Amalia (Jurnal Psikologi, 2017)
Procrastination has an impact on academic achievement, as well as mental health. Although forgiveness is included as an attribute of positive psychology, the evidence about the relationship between forgiveness and procrastination impress contradiction. This study aims to examine the relationship between forgiveness and academic procrastination in college students. There were 127 undergraduate students from The Department of Nutritional Sciences, Faculty of Medicine, University of Diponegoro, Indonesia, who was selected as research subjects using the stratified random sampling technique. Data were collected using The Forgiveness Psychological Scale (32 items, Î± = .888) and The Academic Procrastination Scale (41 items, Î± = .916). The results showed a negative and significant correlation (rxy = -.358, p = .000). The effective contribution is 12.8%. Further results showed negative correlations between forgiveness of self, others, and situations with academic procrastination. The differences in the amount of the contribution of forgiveness between different objects discussed further.Â